DULANG PENAMAT IN SOCIO-RELIGIOUS PRACTICE: INTEGRATION OF ISLAMIC RELIGIOUS EDUCATION, MULTICULTURAL AND LOCAL DEMOCRACY IN THE SASAK COMMUNITY - Nasihin, Sirajun; Hakim, Abdul Azizul; Haris, Abdul; Rasyidi, Abdul Haris; Nasri, Ulyan (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study focuses on the dulang penamat tradition carried out by the Sasak community in Pene and Batu Nampar Villages, with an approach from the perspective of Islamic religious education, multiculturalism, and local democracy. The main objective of this study is to analyze and interpret the meaning of the tradition, not only as a form of cultural preservation, but also as a form of integration of Islamic and multicultural values ​​in the practice of Islamic religious education. This study uses a qualitative method with an field research approach, involving community leaders, families of the deceased and local residents as research subjects. Data were obtained through observation, in-depth interviews, source reviews, documentation analysis and qualitative descriptive analysis. Data analysis techniques were carried out by applying triangulation of sources and methods, which included cross-verification between the results of observations, interviews, and documentation. While descriptive analysis was carried out based on data findings and empirical facts in the field. In addition, interpretations were made of the symbols in the dulang penamat tradition by identifying patterns and meanings related to the integration of tradition with Islamic religious education, multiculturalism and Islamic democracy. The results of the study explain that the dulang penamat tradition that is carried out not only functions as a post-death perfection ritual, but also becomes a means of preserving spiritual values, social interactions and community culture. These existing values ​​then become the basis for the community to maintain this tradition from generation to generation until now. In the process of its implementation, there are values ​​of charity, prayer, and togetherness in tradition. In addition, the values ​​of Islamic democracy such as deliberation and mutual cooperation are reflected in the collective participation of the community. Islamic religious education learning that emerges through this tradition includes the formation of morals, honesty, and responsibility. This study concludes that dulang penamat is a real manifestation of the harmonization between Islamic values ​​and local traditions, which contributes to the preservation of culture and the strengthening of Islamic values ​​and Islamic religious education in a multicultural society